IMPROVING BEGINNING READING SKILLS THROUGH ANIMATED FLASHCARD MEDIA AMONG CHILDREN WITH DISABILITIES - Rani Jayanti; Saifuddin Zuhri; Muhammad Ali Rohmad; Justsinta Sindi Alivi; Amilatus Sholikah (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2026)
Beginning reading skills are fundamental abilities that support children's academic development and communication. However, children with intellectual disabilities often experience difficulties in recognizing letters, associating symbols with sounds, and reading simple words due to limitations in cognitive abilities, attention, and memory. This study aims to describe the improvement of beginning reading skills through animated flashcard media among children with disabilities at SLB ACD Pertiwi Mojokerto City. This study employed a descriptive qualitative approach with seven fourth-grade students with intellectual disabilities aged 10–11 years as research participants. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, data presentation, and conclusion drawing. The results showed that the use of animated flashcard media provided positive developments in students’ beginning reading skills, as indicated by improvements in recognizing simple words, associating pictures with written words, reading words, and increasing students’ attention and involvement during learning activities. Animated flashcard media provided a more concrete learning experience through the combination of pictures and words, helping children with intellectual disabilities understand reading concepts more easily. Furthermore, the use of this media also increased students’ motivation and confidence in participating in reading activities. Based on the findings, animated flashcard media can be considered an alternative instructional medium to support the improvement of beginning reading skills among children with disabilities in special education settings. Keywords: beginning reading skills, animated flashcards, intellectual disabilities